THE STRATEGIES FOR ENHANCING TRANSPORTATION MANAGEMENT AT THE BORDER PORTS BETWEEN MONGOLIA AND CHINA - Munkhzaya Bayanmunkh; Baljinnyam Gungaa; Battsengel Lkhundev; Myangandash Lkhagvaa (World Science, 2024)
Effective management of border port road transport is crucial for enhancing trade and economic potential at border ports and free zones. This involves long-term, medium-term, and short-term planning, as well as the implementation of integrated development policies to ensure sustainable and accessible improvements. By connecting border ports with railways and paved roads, enhancing transport and logistics competitiveness, optimizing cargo flow, and laying the groundwork for future transit capabilities, economic relations and cooperation between Mongolia and China can flourish, fostering the sustainable development of both nations. To boost trade turnover and establish free economic zones and road ports, it is imperative to enhance the management of border port road transport in alignment with Mongolia’s regional development strategy. Currently, the concentration of the economy on only four ports leads to goods shortages, price hikes, and hindered business operations. Therefore, enhancing the type, quality, and availability of road transport services at border ports is essential to increase the throughput capacity of these crucial transportation hubs.